Corneal Curvature Analysis Before and After Phacoemulsification Surgery - Arya, Andi Muhammad; Akib, Marliyanti N; Irsandy, Fabie; Amir, Suliati P; Sofyan, Syukriyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Cataracts cause 33% of preventable visual impairment and also cause 51% of blindness in the world. Phacoemulsification is a surgical technique that is widely performed by ophthalmologists throughout the country. The effects caused after phacoemulsification surgery in the form of diseases caused by corneal curvature defects are astigmatism. This study aims to analyze corneal curvature before and after phacoemulsification surgery. The research method is observational analytic with a cross-sectional approach. The results of the study found that the K1 measurement before surgery had a mean or average value of 43.37. The results of the normality test obtained a p value = 0.770> 0.05 meaning that the K1 data before surgery was normally distributed, while after surgery it was 43.41. The results of the normality test obtained a p value = 0.615> 0.05 meaning that the K1 data after surgery was normally distributed. The K2 measurement before surgery was 44.45. The results of the normality test obtained a p value = 0.742> 0.05, meaning that the K2 data before surgery was normally distributed. The K2 measurement after surgery was 44.32. The results of the normality test obtained a p value = 0.331> 0.05, meaning that the K2 data after surgery was normally distributed. In conclusion, there was no difference between the variables studied, namely the results of keratometry measurements before and after phacoemulsification surgery in cataract patients at the JEC Orbita Makassar Eye Clinic.